Blockade of Orexin Receptors in the Posterior Paraventricular Nucleus of the Thalamus Prevents Stress-Induced Reinstatement of Reward-Seeking Behavior in Rats With a History of Ethanol Dependence - Matzeu, Alessandra; Martin-Fardon, Rémi (Frontiers in Integrative Neuroscience, 2020)
Neural systems involved in processing natural rewards and drugs of abuse overlap and exposure to drugs of abuse induce neuroadaptations that can cause compulsive-like behavior. For example, the recruitment of the orexin (Orx) system by drugs of abuse has been proposed to induce neuroadaptations that in turn alter its function, reflected by maladaptive, compulsive, and addictive behavior. Orexin neurons project to the paraventricular nucleus of the thalamus (PVT)—particularly the posterior part (pPVT), a structure that plays a key role in stress regulation. This study investigated whether Orx transmission in the pPVT plays a role in stress-induced reinstatement of reward-seeking behavior toward ethanol (EtOH) and a highly palatable food reward [sweetened condensed milk (SCM)] in rats and whether this role changes with EtOH dependence. After being trained to orally self-administer EtOH or SCM, the rats were made dependent (EtOHD and SCMD) by chronic intermittent EtOH vapor exposure. The control nondependent groups (EtOHND and SCMND) were exposed to air. Following extinction, the rats were tested for stress-induced reinstatement of EtOH- and SCM-seeking behavior. Stress reinstated EtOH- and SCM-seeking behavior in all groups (EtOHD/ND and SCMD/ND). Administration of the dual Orx receptor (OrxR) antagonist TCS1102 (15 μg) in the pPVT prevented stress-induced reinstatement only in dependent rats (EtOHD and SCMD). In parallel, the qPCR analysis showed that Orx mRNA expression in the hypothalamus and OrxR1/R2 mRNA expression in the pPVT were increased at the time of testing in the EtOHD and SCMD groups. These results are the first to implicate Orx transmission in the pPVT in the stress-induced reinstatement of reward-seeking behavior in EtOH dependent rats and indicate the maladaptive recruitment of Orx transmission in the pPVT by EtOH dependence.